Numerical streamline patterns at swimmer`s surface using RANS equations - Arfaoui, A.; Popa, C. V.; Taiar, R.; Polidori, G.; Fohanno, S. (Journal of Applied Biomechanics, 2012)
The objective of this article is to perform a numerical modeling on the flow dynamics around a competitive female swimmer during the underwater swimming phase for a velocity of 2.2 m/s corresponding to national swimming levels. Flow around the swimmer is assumed turbulent and simulated with a computational fluid dynamics method based on a volume control approach. The 3D numerical simulations have been carried out with the code ANSYS FLUENT and are presented using the standard k-? turbulence model for a Reynolds number of 6.4 × 106. To validate the streamline patterns produced by the simulation, experiments were performed in the swimming pools of the National Institute of Sports and Physical Education in Paris (INSEP) by using the tufts method.